Organizational Factors in the Theory of Oligopoly - Cyert, R. M.; March, James G. (Quarterly Journal of Economics, 1956)
Introduction, 44. — I. Motivational assumptions, 46. — II. The planning process, 49. — III. Organizational slack, 53. — IV. Empirical relevance, 55. — V. Theoretical relevance, 58. — VI. Summary, 62.